Indian Agriculture Towards 2030 Pathways for Enhancing Farmers’ Income, Nutritional Security and Sustainable Food and Farm Systems - Chand, Ramesh; Joshi, Pramod; Khadka, Shyam (India Studies in Business and Economics, 2022)
XV, 311 p. 50 illus., 45 illus. in color.